Pertanggungjawaban Pidana PPAT atas Pemberian Keterangan Palsu dalam Akta Otentik: Studi Putusan Nomor 346/Pid.B/2022/Pn Kla - Edi Agus Yanto (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This normative-juridical study analyzes the criminal liability of a Land Deed Official (PPAT) regarding the forgery of an authentic deed, based on Kalianda District Court Decision No. 346/Pid.B/2022/PN KLA. The central issue lies in the judge's ratio decidendi, which failed to apply the criminal sentencing enhancement for public officials (Article 58 of Law No. 1/2023) regarding the crime of document forgery (Article 444 paragraph 1 of Law No. 1/2023); consequently, the 2.5-year prison sentence failed to provide a deterrent effect or substantive justice for the victim of a land mafia scheme. It is recommended that the Supreme Court issue a Circular Letter establishing specific minimum sentencing guidelines for officials who abuse their authority, and that PPATs mandate biometric verification via the National Land Agency (BPN) application to prevent negligence.